Nothing is as it seems: genetic analyses on stranded fin whales unveil the presence of a fin-blue whale hybrid in the Mediterranean Sea (Balaenopteridae). Issue 1 (31st December 2022) - Fioravanti, T.; Maio, N.; Latini, L.; Splendiani, A.; Guarino, F. M.; Mezzasalma, M.; Petraccioli, A.; Cozzi, B.; Mazzariol, S.; Centelleghe, C.; Sciancalepore, G.; Pietroluongo, G.; et al.
Abstract: The fin whale Balaenoptera physalus is a large rorqual species occurring worldwide, mainly in temperate and subpolar zones. In contrast to many baleen whales, not all the fin whale populations show the same model of migration. In fact, migratory behaviours of this latter species range from long seasonal migration between high and low latitudes to a complete non-migratory behaviour. A resident fin whale population was described in the Mediterranean Sea, which is also frequented by North Atlantic individuals entering through the Strait of Gibraltar in winter to feed. Between 2020 and 2021 three individuals initially identified as fin whales died along the Tyrrhenian coasts (Mediterranean Sea, Italy). Their mitochondrial DNA control region (mtDNA CR) was analysed and compared to fin whale haplotypes previously described in North Atlantic Ocean and Mediterranean Sea to identify their geographical origin. Our results show that two individuals most likely belong to the Mediterranean fin whale population, while an individual was recognised as a putative fin-blue whale hybrid ( Balaenoptera physalus x Balaenoptera musculus ) with a North Atlantic origin. The discovery of the first fin-blue whale hybrid in the Mediterranean Sea was confirmed by the analysis of a biparentally inherited marker, the α-lactalbumin (α-lac) nuclear gene, demonstrating that the morphological analysis alone does not allow to correctly identify hybrids, especially if intermediate characters of both parental species are not clearly distinguishable.